English Result. Intermediate: Photocopiable Resource Book - Godfrey R. Rachel (Oxford, Oxford University Press, 2012)
Photocopiable Resource Book includes: Communicative activities for every main lesson, Worksheets to use in class with the real-world documentary clips and authentic interviews on the Student's DVD, Full teacher's notes for all activities and worksheets, A copy of the Student's DVD for the teacher